2021
DOI: 10.18805/lr-620
|View full text |Cite
|
Sign up to set email alerts
|

​​The Effects of Gibberellic Acid (GA3) Applications on the Physiological Features of Groundnut (Arachis hypogaea L.) under Different Salt (NaCI) Stress Conditions

Abstract: Background: Salinity is one of the most imperative problems of farmers worldwide. Reports are available that the external application of GA3 can reduce harmful effects of salinity. Low concentration and small quantities of GA3, a phytohormone, is essential to hasten the growth and development of plants. The current study was aimed to test the efficiency of GA3 on the impart of salt tolerance in terms of better nutrient uptake under salt stress situation and to determine the effect of external giberellic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Guo et al [ 53 ] showed that the chlorophyll content of gibberellin-treated sesbania plants was higher than the control. Similar results were found by Erbil, who reported that GA 3 application caused a significant increase in chlorophyll content in salt-stressed groundnut plants ( Arachis hypogaea L.) [ 54 ]. The increase in chlorophyll content might be because the application of exogenous GA reduced the enzyme activities involved in chlorophyll catabolism and alleviated the oxidative chlorophyll bleaching, thereby inhibiting chlorophyll catabolism [ 55 ].…”
Section: Effect Of Gibberellins On Physiological Properties Of Sorghu...supporting
confidence: 87%
“…Guo et al [ 53 ] showed that the chlorophyll content of gibberellin-treated sesbania plants was higher than the control. Similar results were found by Erbil, who reported that GA 3 application caused a significant increase in chlorophyll content in salt-stressed groundnut plants ( Arachis hypogaea L.) [ 54 ]. The increase in chlorophyll content might be because the application of exogenous GA reduced the enzyme activities involved in chlorophyll catabolism and alleviated the oxidative chlorophyll bleaching, thereby inhibiting chlorophyll catabolism [ 55 ].…”
Section: Effect Of Gibberellins On Physiological Properties Of Sorghu...supporting
confidence: 87%
“…We found that the transgenic AtrTCP1 and WT Arabidopsis thaliana plants were shorter under salt stress than they were under normal conditions, and they had fewer leaves. Meanwhile, the contents of chlorophyll a, chlorophyll b, and total chlorophyll in the salt-stress-induced plants were lower than those in the non-salt-stress-induced plants because it decreased the leaf chlorophyll content [9]. However, the chlorophyll content of the transformed 35S::AtrTCP1-GUS plants was higher than that of the wild type under salt stress and not under salt stress.…”
Section: Discussionmentioning
confidence: 88%
“…Chlorophyll is the main pigment for photosynthesis in higher plants, and it is directly related to leaf photosynthesis and plant yield potential. Salt stress reduces the leaf chlorophyll content [9]. Chlorophyll fluorescence is closely related to leaf photosynthesis [10], which reflects the effects of environmental factors on plants [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that priming of seeds conferred better stress tolerance against adverse environmental conditions by retaining stress memory thereby enabling protection against oxidative stress ( Jisha et al., 2013 ; Ibrahim, 2016 ; Farooq et al., 2019 ). Groundnut seeds primed with gibberellic acid exhibited higher antioxidant activity, proline, lesser malondialdehyde and higher chlorophyll content under salt stress ( Erbil, 2021 ). Zinc and iron priming significantly enhanced the yield of field-grown groundnut ( Khan et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%